Digital Literacy and Its Impact on English Learning Comprehension: Evidence from Private Higher Education Institutions in Jakarta - Nasywa, A'mmara Nur; Ningsih, Sri Kusuma (Journal of Language and Literature Studies, 2025)
Digital literacy has become a critical competency for students in higher education, particularly in English language learning, where technology increasingly shapes access to resources and modes of comprehension. This study investigates the impact of digital literacy on students’ English learning comprehension in private higher education institutions in Jakarta. Using a quantitative research design, data were collected from 195 respondents enrolled in an English Language Education program through questionnaires distributed online. The instrument assessed students’ self-reported digital literacy competence, frequency of digital tool usage, and perceived impact on English comprehension. Data were analyzed using descriptive statistics and simple linear regression. The results demonstrate that digital literacy significantly influences students’ comprehension in digital-based English learning. Regression analysis revealed that the frequency of using digital technology explained 20.7% of the variance in comprehension (Model 1, R² = 0.207, p < 0.01), while inclusion of demographic variables increased the explanatory power to 32.8% (Model 2, R² = 0.328, p < 0.01). However, factors such as gender, age, semester level, and prior English learning experience did not significantly predict comprehension outcomes. Students with higher digital literacy reported greater confidence, motivation, and ability to evaluate and apply online resources effectively. These findings confirm that digital literacy is a key determinant of English learning success, extending beyond technical skills to include attitudes and critical engagement with digital content. The study suggests that integrating digital literacy training into English curricula can enhance learning outcomes, foster autonomy, and align education with contemporary digital practices.